Factors Facilitating and Hindering the Use of Newly Acquired Positioning Skills in Clinical Practice: A Longitudinal Survey - Ludwig, Vera U.; Pickenbrock, Heidrun; Döppner, Daniel A. (Frontiers in Medicine, 2022)
Background After learning new skills, healthcare professionals do not always apply them in practice, despite being motivated. This may be referred to as an intention-behavior gap. One example is the positioning of immobilized and disabled patients in hospitals, nursing homes, or neurorehabilitation clinics. Positioning is crucial to prevent complications such as pressure sores, pneumonia, and deep vein thrombosis. However, it is often not carried out optimally even when professionals have completed education programs. The LiN-method is a positioning procedure involving a special focus on aligning and stabilizing body parts, which has been shown to have advantages over conventional positioning. We assess which factors may facilitate or hinder the use of LiN in clinical practice after participants complete training. Methods A longitudinal survey with 101 LiN-course participants was conducted in Germany. Each participant completed a questionnaire directly after the course and 12 weeks later, including a report of the frequency of use in practice. They also completed a questionnaire which surveyed 23 aspects that might facilitate or hinder use of the new skills, covering the workplace, socio-collegial factors, motivation, self-confidence, and mindset. Results Most assessed aspects were associated with LiN-use, with the highest correlations found for confidence with the method, perceived ease of application, sufficient time, assessing one's skills as sufficient, remembering the relevant steps, and a work environment open to advanced therapeutic concepts. To reduce data complexity, the questionnaire was subjected to a factor analysis, revealing six factors. A regression analysis showed that four factors predicted use 12 weeks after course completion, in the following order of importance: (1) subjective aspects/confidence, (2) access to materials, (3) work context, and (4) competent support in the workplace. Conclusion Numerous aspects are associated with the use of recently acquired clinical or nursing skills, such as LiN. Many of these can be improved by appropriately setting up the workplace. The aspects most associated with use, however, are confidence with the method and self-perceived competence of healthcare professionals. While causality still needs to be demonstrated, this suggests that education programs should support participants in developing confidence and foster a mindset that allows for making mistakes.